Memory maps : the state and Manchuria in postwar Japan - Tamanoi, Mariko (World of East Asia., 2009)
This work tells how between 1932 and 1945, more than 320,000 Japanese emigrated to Manchuria with the dream of becoming land-owning farmers. However, following the Soviet invasion of Manchuria and Japan's surrender in August 1945, their dream turned into a nightmare.